Dinámicas de incorporación y exclusión social. Guaraníes en las fronteras del capital - Literas, Luciano (Revista de Antropología Social, 2008)
This work analyzes dynamics of incorporation and exclusion in historical perspective personified in the social and geographical local space; guidelines of social and productive organization that reigned in agreement to the constitution, joint and disappearance of manners of producing and distributing resources. The intention is to describe and to analyze the genealogy of the current exclusion of ethnic rural sectors: how and why does one live in the exclusion? I take de ava guaraní case and ther relations with the sugar industry in the high basin of the Bermejo river, province of Salta, Argentine- Bolivian border. The effective control of this region did not was happen during the colonial period; the break of interior borders took place at the end of 19th century and beginnings of the XXth through private institutions -with fundamental role in the exercise of economic and politic hegemony- that they orchestrated the territorial expansion and incorporation of workforce. Dynamics that then will constitute the beginning of marginality and exclusion of the local groups, base of their ethnic recovery.
Keywords: Exclusion; Pluswork; Ethnic group; Large estate; Unemployment